Determinan Kemiskinan Rumah Tangga di Jawa Timur - Angga Erlando; Tri Haryanto; Verliana Rositawati (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
This study aims to determine the economic, demographic, and social characteristics that are determinants of poverty, and analyze how the level of tendency (probability) in shaping poverty in East Java. Using a quantitative approach, this research relies on a logistical model (logit). The logit model aims to find the probability of an event occurring, in this case the probability of a household heading into poverty or not. The result is that education of household heads, gender of household heads, household size, household head work sector, access to KUR, and access to poor health insurance have a tendency to be determinants for household heading to poverty status. Educational variables, gender of the head of household, and access to KUR from this paper empirically show a tendency to reduce the probability of households to poor. Meanwhile increasing household size, types of employment in the agricultural sector, and the ownership of poor health insurance tend to increase theprobability of households heading into poverty status.